2001
DOI: 10.1079/bjn2001363
|View full text |Cite
|
Sign up to set email alerts
|

Feeding tuna oil to the sow at different times during pregnancy has different effects on piglet long-chain polyunsaturated fatty acid composition at birth and subsequent growth

Abstract: In an attempt to prevent decreases in piglet 20 : 4n-6 status at birth while increasing 22 : 6n-3 status, multiparous sows (eight per treatment) were allocated to one of three different treatments: a basal diet fed from day 63 of pregnancy to term; basal diet supplemented with tuna oil (17´5 g/kg) from day 63 to day 91 and then basal diet alone from day 92 to term; basal diet alone from day 63 to day 91 and then basal diet supplemented with tuna oil from day 92 to term. Tuna oil supplementation increased mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
54
3
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 25 publications
13
54
3
2
Order By: Relevance
“…BW from birth until the end of the nursery period (34 days after weaning) tended to be higher in litters from n-3 LCPUFA fed sows in the present study, again consistent with earlier studies (Rooke et al, 2000 and2001b;Mateo et al, 2009). As Taugbol et al (1993 and Fritsche et al (1993) did not find an effect on weaning weight when n-3 LCPUFA supplementation started at day 107 of gestation, and Smits et al (2011) did not find an effect on piglet growth and weaning weight when feeding n-3 LCPUFAs from 8 days before farrowing, longer periods of supplementation may be needed in gestation to produce positive effects on litter weaning weight.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…BW from birth until the end of the nursery period (34 days after weaning) tended to be higher in litters from n-3 LCPUFA fed sows in the present study, again consistent with earlier studies (Rooke et al, 2000 and2001b;Mateo et al, 2009). As Taugbol et al (1993 and Fritsche et al (1993) did not find an effect on weaning weight when n-3 LCPUFA supplementation started at day 107 of gestation, and Smits et al (2011) did not find an effect on piglet growth and weaning weight when feeding n-3 LCPUFAs from 8 days before farrowing, longer periods of supplementation may be needed in gestation to produce positive effects on litter weaning weight.…”
Section: Discussionsupporting
confidence: 93%
“…This confirms that either DHA is taken up through the placenta into the embryo during early pregnancy or that more EPA was taken up by the embryo and then converted to DHA. As tissues of pigs from n-3 LCPUFA supplemented sows also showed higher EPA and DHA levels at birth than pigs from Control sows (Rooke et al, 2001b and2001c), it is likely that n-3 LCPUFA uptake continues throughout gestation, although Amusquivar et al (2010) showed that n-3 LCPUFA levels were increased in sow milk and pig plasma when sows were only supplemented with n-3 LCPUFA during the first half of gestation (days 1 to 60), suggesting that n-3 LCPUFAs can be stored in maternal adipose tissue and mobilized during milk production. When sows were supplemented with n-3 LCPUFAs in gestation and lactation, n-3 LCPUFA levels were also higher in colostrum and milk (Taugbol et al, 1993;Rooke et al, 2000 and2001a).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As discussed by Smit et al (2013a), interpretation of effects of mLCPUFA treatment on survivability may be difficult due to confounding effects of gestation length and the use of induced farrowing, as was again the practice in the present trial. Although brain weight was not different between treatments (Smit et al, 2014), the DHA concentration in brain tissue was higher in stillborns from mLCPUFA-fed sows compared with controls, which is in agreement with other research (Rooke et al, 2000 and2001a), and was not surprising considering the importance of DHA for brain development (Innis, 2007). Higher DHA levels in the brain could lead to increased postnatal growth rates due to a change in behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Recent work has shown that feeding fish oil, as a source of long-chain n-3 FAs, during gestation improved the viability of the neonate in monogastric (Rooke et al, 2001) and in ruminant animals (Dawson and Edgar, 2005;Capper et al, 2006). However, the importance of period of inclusion of n-3 FAs in gestation diets has not yet been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%